The relationship between metabolic acidosis, lactate, the lactate:pyruvate ratio, and outcome, in children with post-operative cardiogenic and septic shock - Hatherill, Mark (Department of Paediatrics and Child Health, 2015)
Includes bibliographical references (leaves 106-112).